Determinants of Green Innovation to Achieve Sustainable Business Performance: Evidence From SMEs - Baeshen, Yasser; Soomro, Yasir Ali; Bhutto, Muhammad Yaseen (Frontiers in Psychology, 2021)
Environmental degradation and global warming are major challenges to humankind in the 21st century. Thus, businesses are now adopting and incorporating more sustainable manufacturing methods to produce environmental products and services. It is inevitable for organizations to adopt green practices and achieve sustainable performance. This extant research addresses how to obtain Sustainable Development (SD) through green innovation. The main purpose of this study is to develop a comprehensive model by integrating natural resource-based view (NRBV) and triple bottom line (TBL) framework. Three antecedents namely Green Absorptive capacity (GAC), Sustainable Human Capital (SHC), and Organization support (OS) were selected and their influence was checked on green innovation (GRIN) of the SMEs from manufacturing sector. This study included all three factors of Triple bottom line: environmental, economic, and social sustainability in terms of green innovation's possible consequences. Data was randomly collected from 304 firms in the kingdom of Saudi Arabia through questionnaire. Convergent and discriminant validity analyses were conducted to assure validity and reliability, and structural equation modeling (SEM) was utilized to assess the relationships between variables using smartPLS 3.0 software. Further, firms were categorized into two groups based on company size—small and medium—to explore group differences. Hence, firm size was included as a moderator in the proposed model and multi-group analysis (MGA) was performed. The results indicate that GAC, SHC and OS have positive influence on GRIN within SMEs. Further, results reveal GRIN had strong significant impact on all three variables of sustainable performance. The study concludes with MGA results that provided evidence of significant group differences, with a stronger relationship between GAC and GRIN in medium-sized firms compared to small-sized firms. Similarly, the relationship between GRIN and environmental performance was stronger in medium-sized firms than small-sized firms. This study is unique and provides practical and theoretical implications. This paper offers an integrative model for sustainability which may be of interest to scholars, marketers, and policymakers.